SOD2 is a C-myc target gene that promotes the migration and invasion of tongue squamous cell carcinoma involving cancer stem-like cells. (March 2015) - Liu, Zhonghua; He, Qianting; Ding, Xueqiang; Zhao, Tingting; Zhao, Luodan; Wang, Anxun
Graphical abstract: Highlights: Cancer stem-like cells play an important role in TSCC migration and invasion. SOD2 mediated TSCC migration and invasion involve cancer stem-like cells. C-myc directly targets and regulates the expression of SOD2. C-myc-SOD2 pathway mediates TSCC migration and invasion involving CSCs. Abstract: Our previous studies revealed that manganese superoxide dismutase (SOD2) contributes to the migration and invasion of tongue squamous cell carcinoma (TSCC). The purpose of the current study was to further clarify the mechanisms of SOD2 in the migration and invasion of TSCC. Side population (SP) cells were used as cancer stem-like cells and further assessed by sphere and colony formation assays, and the expression of stem cell markers (Bmi1, Nanog and ABCG2). We found that UM1 cells (TSCC cells with increased SOD2 expression, migration and invasion abilities) possessed a higher proportion of SP cells, sphere and colony formation, and expressed a higher level of stem cell markers compared to UM2 cells (reduced SOD2 expression, migration and invasion abilities). SOD2 expression as well as migration and invasion abilities were enhanced in SP cells compared to non-SP cells. Knockdown of SOD2 in UM1 cells or SP cells inhibited the migration and invasion abilities, reduced sphere and colony formation, and the expression of stem cell markers. Direct binding of the C-myc protein to the SOD2 promoter was demonstrated by chromatin immunoprecipitation and luciferase assays. Knockdown of C-myc in UM1 cells inhibited SOD2 expression as well as migration and invasion abilities. Our results indicate that cancer stem-like cells play an important role in the migration and invasion of TSCC. SOD2 is a direct target gene of C-myc and C-myc-SOD2-mediated migration and invasion of TSCC involve cancer stem-like cells.